2022
DOI: 10.1002/gcc.23073
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of copy number alterations by liquid biopsy for neuroblastoma

Abstract: Liquid biopsy, a method of detecting genomic alterations using blood specimens, has recently attracted attention as a noninvasive alternative to surgical tissue biopsy. We attempted quantitative analysis to detect amplification of MYCN (MYCNamp) and loss of heterozygosity at 11q (11qLOH), which are clinical requisites as prognostic factors of neuroblastoma (NB). In this study, cell‐free DNA (cfDNA) was extracted from plasma samples from 24 NB patients at diagnosis. Copy numbers of MYCN and NAGK genes were quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…Therefore, external references with variations in PCR efficiency are not necessary anymore ( 11 ). It has been used in a lot of clinical fields, such as liquid biopsies for cancer monitoring and noninvasive prenatal testing for genetic abnormality detection ( 12 14 ). Recently, ddPCR has shown promising potential in resolving polymicrobial infection since it simultaneously achieves unprecedented high sensitivity (able to detect pathogens at low concentrations of as few as 10 CFU/mL) in an about 4-h turnaround time ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, external references with variations in PCR efficiency are not necessary anymore ( 11 ). It has been used in a lot of clinical fields, such as liquid biopsies for cancer monitoring and noninvasive prenatal testing for genetic abnormality detection ( 12 14 ). Recently, ddPCR has shown promising potential in resolving polymicrobial infection since it simultaneously achieves unprecedented high sensitivity (able to detect pathogens at low concentrations of as few as 10 CFU/mL) in an about 4-h turnaround time ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, new nucleic acid detection techniques have been used to detect pathogenic microorganisms. Droplet digital PCR (ddPCR) is a method of absolute nucleic acid quantification by using Poisson statistical analysis of the number of positive and negative droplets and has been proven to achieve higher accuracy and sensitivity than qPCR ( Shirai et al., 2022 ). It has been used in a lot of clinical fields, such as liquid biopsies for cancer monitoring and noninvasive prenatal testing for genetic abnormality detection( Cainap et al., 2021 ; Boldrin et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…29 Additionally, liquid biopsy studies have demonstrated that cellfree DNA (cfDNA) is a sensitive method of detecting minimal residual disease (MRD) in adult cancers and has been used for risk stratification in adult clinical trials. 30 Liquid biopsy could likewise be applied in neuroblastoma patients, 31 where cfDNA could be used to guide intensification or de-intensification of treatment as children progress through therapy, with the aim to reduce the burden of late effects if a good MRD response is obtained. It is important to emphasize that current risk stratification and treatment strategies need to be improved to reduce the significant burden of late effects to allow for improved patient management, with the hope that modern MRD techniques and molecularly targeted agents will inform future customized therapies.…”
Section: Discussionmentioning
confidence: 99%